The equation given is in vertex form, \(y = a(x - h)^2 + k\), where \((h, k)\) is the vertex.
From the equation \(y = -2(x - 13)^2 + 47\):
- \(h = 13\)
- \(k = 47\)
Therefore, the vertex is \((13, 47)\).
The correct response is: (13, 47).
.(1 point)
Responses
(13,47)
left parenthesis 13 comma 47 right parenthesis
(−13,47)
left parenthesis negative 13 comma 47 right parenthesis
(−2,47)
left parenthesis negative 2 comma 47 right parenthesis
(26,47)
1 answer
The equation given is in vertex form, \(y = a(x - h)^2 + k\), where \((h, k)\) is the vertex.
From the equation \(y = -2(x - 13)^2 + 47\):
Therefore, the vertex is \((13, 47)\).
The correct response is: (13, 47).